PRODUCTION OF AUSTRALIAN CEDAR SEEDLINGS INOCULATED WITH ARBUSCULAR MYCORRHIZAL FUNGI IN DIFFERENT TYPES OF CONTAINERS - Élida Ribeiro do Carmo (Revista Árvore, 2016)
ABSTRACT The present study aimed to evaluate the growth and the levels of N, P, K, Ca and Mg in Australian cedar seedlings which had been inoculated with arbuscular mycorrhizal fungi (AMF) in different types of containers. The experiment was carried out in a greenhouse and the experimental design was that of randomized complete blocks (RCB), with a 4 x 4 factorial design consisting of four inoculation treatments with AMF (Rhizophagus clarum, Gigaspora margarita, a mixed inoculation (R. clarum + G. margarita) and the control (with no AMF inoculation); four types of containers (plastic bags measuring 250 cm3, tubes of 55 and 130 cm3 and pressed blocks 440 cm3. plant-1), with four repetitions. The height, the diameter of the stem base, the aerial part dry weight (APDW), the dry weight of the root (DWR) and the total plant dry weight (DW) were measured, along with the Dickson quality index, the percentage of mycorrhizal colonization and the levels of N, P, K, Ca and Mg in the aerial part dry weight. One hundred and thirty eight days (138) days after sowing, the greatest growth and/or the highest levels of P, K and Ca could be observed in the aerial part dry weight of the Australian cedar seedlings which had been planted in the pressed block container and inoculated with a mixture of the two AMF species (G. margarita + R. clarum) or with just R. clarum. Thus it can be seen that AMF can make a significant contribution to the production of Australian cedar seedlings.